Vehicle Loading and Unloading Activities at MV Aishakamilah, Hazard Identification, Risk Assessment and Risk Control - Usman, Arif Fuddin; Asmarita, Sri; Murtafiah, Andi; Ningrat, Andi; Sudarman (Indonesian Journal of Maritime Technology, 2024)
This research is to determine risk control from the results of identifying hazards that are likely to occur in loading and unloading activities on the MV. Aishakamila. The informans in this study were operational workers and crew of Kalla Lines at the port totaling 20 people with the Purposive Sampling technique. The results of this study found that the identified hazards in the loading and unloading process at PT. Bumi Lintas Tama, there were 21 identified hazards. The results of the risk assessment obtained from the 21 identified hazards from the loading and unloading process activities on the MV. Aishakamilah at the PT. Bumi Lintas Tama Car Terminal, there were results from the risk level after control was carried out, namely the High Risk level of 0 risks, the Moderate Risk level of 3 and the Low Risk level of 18 risks. From the observations conducted by researchers in the field, the loading and unloading activities on the MV. Aishakamila have 4 risk control hierarchies applied. The risk controls applied are substitution, engineering, administration, and personal protective equipment. From the results of the study, a way to reduce the level of risk of danger in vehicle loading and unloading operations on the MV. Aishakamilah is obtained by conducting a briefing before carrying out loading and unloading activities and always paying attention to PPE in working and paying attention to applicable SOPs